Myelofibrosis and angiodysplasia of the colon: another manifestation of portal hypertension and massive splenomegaly?. Issue 9 (27th August 2004) - Biss, T; Hamilton, P
Abstract : Bleeding owing to portal hypertensive colopathy, a form of large bowel angiodysplasia, as a cause of increased blood transfusion requirement is described in a 74 year old man with idiopathic myelofibrosis. The proposed mechanism and the potential therapeutic options for this rare complication of myelofibrosis are discussed.